Virtualisation of an administrative work environment in higher education: Managing information in a developing country university. Issue 5 (11th September 2017) - Adam, Ibrahim Osman; Effah, John; Boateng, Richard
Abstract : Purpose: The purpose of this paper is to understand how higher education institutions (HEIs) in developing countries can migrate their physical administrative work environment to a virtual platform to improve information management. Design/methodology/approach: The paper employs an interpretive case study approach and a combined lens of activity and agency theories to understand how a developing country HEI attempted to improve its information management by migrating from a physical to a virtual administrative work environment. Findings: The findings show how contradictions caused by role conflicts, administrative staff's fear of elimination and external consultants' limited understanding of administrative rules and procedures can hamper work environment virtualisation. Such challenges should be resolved in order to achieve a successful virtual work environment that supports timely and accurate information management. Research limitations/implications: The study is limited by its single case perspective in one developing country. However, future studies can compare the experiences of HEIs from developed and developing countries in order to account for contextual differences. Practical implications: The study provides practitioners with insight into how to address conflicts between employees (as potential users) and external consultants during virtual system development and implementation. In particular, role conflict, fear of eliminating some administrative staff and consultants' limited understanding of administrative work procedures should be resolved for successful work environment virtualisation. Originality/value: The study is the first attempt to offer rich insight into the challenges associated with administrative work environment virtualisation for improved information management in HEIs, through the principal-agent relationship.